Extended safety and efficacy studies of a live attenuated double leucine and pantothenate auxotroph of Mycobacterium tuberculosis as a vaccine candidate - Sampson, Samantha L. (2011)
We have previously described the development of a live, fully attenuated Mycobacterium tuberculosis (Mtb) vaccine candidate strain with two independent attenuating auxotrophic mutations in leucine and pantothenate biosynthesis. In the present work, those studies have been extended to include testing for protective efficacy in a long-term guinea pig survival model and safety testing in the highly tuberculosis susceptible Rhesus macaque. To model the safety of the ΔleuD ΔpanCD strain in HIV-infected human populations, a Simian Immunodeficiency Virus (SIV)-infected Rhesus macaque group was included. Immunization with the non-replicating ΔleuD ΔpanCD conferred long-term protection against challenge with virulent M. tuberculosis equivalent to that afforded by BCG as measured by guinea pig survival. In safety studies, clinical, hematological and bacteriological monitoring of both SIV-positive and SIV-negative Rhesus macaques immunized with ΔleuD ΔpanCD, revealed no vaccine-associated adverse effects. The results support the further development of the ΔleuD ΔpanCD strain as a viable tuberculosis (TB) vaccine candidate.